Interações magnéticas e elétricas em GaMnAs - Pedrosa, Gabriel Teófilo Dias (2016)
In this paper, we will address together the magnetic and electrical properties of a particular semiconductor, the GaMnAs. The treatment will be done analytically in the first part of the work, according to the computational method for simulation of physical systems through the implementation of the expressions obtained in the first part. All study of magnetic contribution will be made using an interaction Kondo type, using an approach by Green functions. The electrical part, which consists of the Coulomb interactions between carriers and Mn ions, will be treated within the approach of multiple scattering. The implementation of the proposed method will calculate the Green functions converged as multiple scattering solution and use them as a starting point for the calculation of the effective magnetic interactions between Mn ions mediated charge carriers. The concentration parameters were varied for Mn ions and carriers as well. The combination of these two parameters can lead to insulating, metal samples with carriers in Fermi level to low or high mobility. As a result a correlation between the obtained carrier mobility and the strength of magnetic interaction. The greater mobility, the greater the intensity of the interaction.